3x-(4x+6)=x-9

Simple and best practice solution for 3x-(4x+6)=x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(4x+6)=x-9 equation:


Simplifying
3x + -1(4x + 6) = x + -9

Reorder the terms:
3x + -1(6 + 4x) = x + -9
3x + (6 * -1 + 4x * -1) = x + -9
3x + (-6 + -4x) = x + -9

Reorder the terms:
-6 + 3x + -4x = x + -9

Combine like terms: 3x + -4x = -1x
-6 + -1x = x + -9

Reorder the terms:
-6 + -1x = -9 + x

Solving
-6 + -1x = -9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -1x + -1x = -9 + x + -1x

Combine like terms: -1x + -1x = -2x
-6 + -2x = -9 + x + -1x

Combine like terms: x + -1x = 0
-6 + -2x = -9 + 0
-6 + -2x = -9

Add '6' to each side of the equation.
-6 + 6 + -2x = -9 + 6

Combine like terms: -6 + 6 = 0
0 + -2x = -9 + 6
-2x = -9 + 6

Combine like terms: -9 + 6 = -3
-2x = -3

Divide each side by '-2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 | | 8-2w=-w | | -6n=-6-7n | | 8r+10=9r | | 1/5n=-8 | | 2r+3(r+3)+3r=1 | | x^2+18x+73=-9 | | y=-4.9t^2+120t | | 270=920(1-d) | | 8.7=3.5m-3.5(5.4-6m) | | 4a+5(a+3)+-14=64 | | -10-3p=10-5p-8 | | 4m^2n-6n^2-2mn= | | 3(5z+1)-12=13z+3 | | -2-6=-8u | | -4=3x+6 | | 110-x=113 | | -9t-10=t |

Equations solver categories